Analysis of the association between Epstein-Barr virus and classic Hodgkin's lymphoma in adult patients from Ceará (Brazil) by immunohistochemistry and in situ hybridization Análise da associação do vírus Epstein-Barr com a forma clássica do linfoma de Hodgkin em adultos do estado do Ceará: avaliação por imuno-histoquímica e hibridização in situ - Marília Taumaturgo Pinto; Francisco Valdeci de Almeida Ferreira; Maria da Silva Pitombeira; Silvia Maria Meira Magalhães; Clara Maria Bastos Eloy da Costa; Paulo Wagner Linhares Lima Filho; Renata Praciano Correia Férrer; Andrei Levine Porfírio de Aguiar; Francisco Dário Rocha Filho (Sociedade Brasileira de Patologia Clínica, 2006)
The prevalence of Epstein-Barr virus (EBV) in patients with classical Hodgkin's lymphoma (CHL) is geographically variable. In the present study the prevalence of EBV in CHL was assessed in adult patients from Ceará, Brazil. Thirty-seven cases were immunohistochemically evaluated for EBV using latent membrane protein (LMP1) antibody and for EBV latency-associated RNA (EBER1) using in situ hybridization (ISH). Sex and age did not differ among patients as to the frequency of CHL. Nodular sclerosis was the predominant histological subtype. LMP1 was found in Reed-Sternberg cells in 67.5% of the cases whereas ISH detected EBER1 in 75.6%. Regarding histological subtypes EBV infection rates were not found statistically different in nodular sclerosis (NS) and mixed cellularity (MC) subtypes (p = 0.66). A freqüência do vírus Epstein-Barr (EBV) em pacientes com linfoma de Hodgkin Clássico (LHC) sofre variabilidade geográfica. No presente estudo investigamos a freqüência do EBV em pacientes com LHC no estado do Ceará. Trinta e sete casos de linfoma de Hodgkin clássico foram avaliados por imuno-histoquímica para EBV usando o anticorpo monoclonal contra a proteína latente da membrana (LMP1) e pelo método de hibridização in situ para RNA associado ao EBV (EBER1). Não há diferença por sexo e idade dos pacientes no que concerne à freqüência de LHC. O subtipo histológico esclerose nodular foi predominante. LMP1 esteve presente em células Reed-Sternberg em 67,5% e pela hibridização in situ, através da sonda EBER, foi evidente em 75,6% dos casos. Não observamos predominância significativa da associação de EBV com os subtipos histológicos esclerose nodular (EN) e celularidade mista (CM) (p = 0,66).